Вплив левотироксину на стан оксидантно-антиоксидантного балансу у пацієнтів з поєднаним перебігом артеріальної гіпертензії, цукрового діабету 2 типу та субклінічного гіпотиреозу - Немцова, Валерія Даниілівна (Полтавський державний медичний університет, 2019)
У 40 пацієнтів з поєднаним перебігом артеріальної гіпертензії (АГ), цукрового діабету 2 типу (ЦД2Т) та субклінічного гіпотиреоза (СГТ) при рівні ТТГ в діапазоні 6.0-10,0 мкМОд/мл має місце виражена стимуляція окислювальних процесів на тлі пригнічення антиоксидантної системи. Призначення левотироксину супроводжувалось недостовірним зниженням рівнів малонового діальдегіду та 8-гідроксі-2-дезоксигуанозину наприкінці терміну спостерігання (1 рік), та вірогідним підвищенням рівня глутатіонпероксидази (р=0,016) та сульфгідрильних груп (р=0,001), що свідчить про покращення оксидантно-антиоксидантного балансу за рахунок інтенсифікації захисних антиоксидантних механізмів в більшій мірі, ніж за рахунок пригнічення окислювальних процесів.

Aim: to evaluate the effect of levothyroxine replacement therapy on oxidative stress in patients with combined course of arterial hypertension (AH), type 2 diabetes mellitus (DM2T), and subclinical hypothyroidism (SHT). Object and methods.The study included 40 patients (9 males and 31 females) aged 44 to 75 years (mean age 59.3 ± 3.5 years) with stage II hypertension in combination with DM2T and SHT. The presence of SHT that developed as a result of autoimmune thyroiditis (AIT) and TSH levels in the range 6.0-10.0 µMU/ml in screening was an obigatory criterion. The control group consisted of 30 gender and age-representative patients who did not have cardiovascular disease and endocrinopathies. Thyroid metabolism, glutathione peroxidase (GPO) activity, levels of sulfhydryl groups (SH-groups), malonic dialdehyde (MDA) and 8-hydroxy-2-deoxyguanosine (8-OH-dG) in serum were determined. Ultrasound examination of the thyroid gland was performed on the “LOGIQ 5” according to the standard method. After determining the TSH level, patients were prescribed levothyroxine at doses of 12.5 to 50 μg/day with gradual dose titration (21 day titration step) until euthyroidism was achieved. Observation period was1 year. Statisti-cal processing of data was performed using the computer program SPSS 21.0. Results. The presence of significantly higher levels of MDA and significantly elevated (almost 2.3-fold) levels of 8-OHdG in the patients of the study group indicates a pronounced stimulation of oxidative processes in such a poly-morbid clinical situation. Stimulation of the oxidation processes occurs against the background of inhibition of the antioxidant system, which is manifested by a significantly decrease in levels of both GPO (p <0.05) and SH-groups (p <0.05). Correlation analysis revealed a positive association between TSH and GPO levels (r = 0.226, p = 0.029) and a negative relationship between TSH and SH group levels (r = -0.227, p = 0.028). Conducting a one-way ANOVA revealed the presence of an effect of TSH levels on the level of GPO (p = 0.039) in this category of patients. The administration of levothyroxine was accompanied by a decrease in MDA and 8-OHdG levels at the end of the observation period, although these changes were unreliable, and a significant increase in the antioxidant protection indexes – GPO (p = 0.016) and SH-groups (p = 0.001). Conclusions. The presence of a combined course of arterial hypertension, type 2 diabetes and subclinical hypo-thyroidism with TSH in the range 6.0-10.0 µMUd/ml is accompanied by the presence of pronounced oxidative stress. Prescribing levothyroxine replacement therapy to patients with such polymoride pathology leads to an improvement in the oxidant-antioxidant balance by intensifying the antioxidant defense mechanisms to a greater extent than by inhibiting the oxidative processes.
Levothyroxine on the state of oxidant-antioxidant balance in patients with com-bined course of hypertension, type 2 diabetes and subclinical hypothyroidism
Keywords: артеріальна гіпертензія; цукровий діабет 2 типу та субклінічний гіпотиреоз; левотироксин; оксидативний стрес; hypertension; type 2 diabetes; subclinical hypothyroidism; levothyroxine; oxidative stress